Horner syndrome as a postoperative complication of thyroid surgery: a systematic review - Xie, Tianhao; Fu, Yan; Jin, Xiaoshi; Meng, Qingxu; Liu, Yang; Liu, Xiaoshuang; Niu, Zheng; Sun, Xinli; Liu, Lingyun (Frontiers in Endocrinology, 2025)
ObjectiveThis systematic review aims to enhance surgeons’ awareness of Horner Syndrome (HS) as a rare yet significant complication following thyroid surgery (TS).Data sourcesWeb of Science, PubMed, Cochrane Library, and Embase.Review methodsBased on the PRISMA framework, a comprehensive literature search was conducted covering the period from January 1, 2000, to June 1, 2025.ResultsOut of the 308 articles retrieved, 50 were included in this review, comprising 14 case series and 36 case reports. These studies documented a total of 40 cases of HS following TS. The overall incidence of HS was found to be 0.25%, with a higher incidence in open surgery (0.41%) compared to endoscopic surgery (0.15%). The incidence rate among children undergoing open surgery was 1.84%, which was higher than that among adults (0.22%). Malignant cases accounted for 67.5%, while benign cases represented the remaining 32.5%. HS symptoms typically manifested within 3 days post-surgery, with ptosis being the most common presentation. It rarely affects ocular function but may lead to decreased vision or heterochromia. Short-term steroid and neurotrophic therapy demonstrated some efficacy in alleviating symptoms, and complete recovery was more likely to occur within one year.ConclusionHS represents a rare yet significant complication of TS, primarily attributed to surgical trauma to the cervical sympathetic chain (CSC). Clinicians must remain vigilant regarding this complication and employ meticulous surgical techniques to prevent CSC injury.